A dark intruder – primary oral mucosal melanoma - Kumar, Harish; Dhinesh; Doley, Pooja; Akhila, Kuttappan; Bhardwaj, Abhishek; Rao, Shalinee; Gupta, Sweety (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Oral mucosal melanoma is an infrequent and rapidly progressive malignancy, accounting for approximately 0.5% among all oral cancers, and is associated with poor prognosis. It is frequently detected at an advanced stage, often with involvement of regional lymph node, due to its rapid progression and painless initial phase. The primary treatment is surgical excision, often followed by adjuvant radiotherapy, chemotherapy, or immunotherapy which lowers the risk of recurrence and distant metastasis. In this article, we describe a patient with oral mucosal melanoma of the left superior gingivobuccal sulcus, managed with palliative radiotherapy followed by chemotherapy due to inoperability and financial constraints. A brief review of the literature is also included.